Status of Aquarium Fisheries of Rajshahi City (Journal of Bio-Science, 2009)
An aquarium is an enclosed body of water containing a mixture of selected and unselected captive living aquatic organism. It is essentially unstable and to obtain stability must be carefully designed and managed (Suxena 2003). Recently aquarium technology means that the technical problems of keening aquatic animals have in principle been solved. It includes about water preparation and the constant monitoring of water quality i.e. pH, hardness, dissolve oxygen, temperature etc. and for this heater, pumps and filter is used. For first time colorful fishes are imported in our country in 1992 and the business was confined in some limited shops of Katabaon area of Dhaka city. But now this business is very common in all over the country (Akhter 1995). It is not only enhancing the beauty of a house but also it is a source of recreation. Japanese can realize the presage of earthquake or can predict about natural disaster by watching the sudden movement of the aquarium fishes (Shafi 1998). Similarly to get rid of mental stress, watching fish is reported well and this also helps to decrease the high blood pressure (Hervert 1999). In Rajshahi city aquarium business started at the last decade and it is spreading rapidly. So development of aquarium fisheries is highly significant here. Â  doi: 10.3329/jbs.v15i0.2159 J. bio-sci. 15: 169-171, 2007